Study on The Nurul Quran Method at The Syakirin Center of Al-Qur’an Education - Wahid, Abd.; Mahmud, Nursyahindah Binti; Asnawiyah, Asnawiyah; Nazaryani, Nazaryani (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Every believer is obligated to possess the ability to read the Quran proficiently. This obligation extends not only to adults but is also encouraged from a young age, ensuring that children learn the sacred verses of the Quran. The significance of this mandate is earnestly acknowledged by the Youth Department of the Pan-Malaysian Islamic Party (PAS), which has established several renowned Quranic Education Centers throughout Malaysia. These educational centers have received widespread recognition and are considered pioneers in the establishment of Quranic Education Centers (TPA). Over the past half-century since its inception, TPA has continued to evolve, employing a teaching methodology known as the